The Role of Supply Chain Management on Consumer Service Innovativeness and Consumer Attitude - Kristiningsih Kristiningsih; Sri Hartini; Indrianawati Usman (International Journal of Supply Chain Management, 2020)
Abstract- This research tried to discuss the supply chain management and its motivation, ability, and opportunity on consumer service innovativeness and consumer attitude. The aimed of this research was threefold. First of all, this research reviewed phenomena on motivation, opportunity, and ability on consumer innovativeness. Second, we developed a measurement that important to the research which discussed about motivation, ability, and opportunity on consumer innovativeness. Third, we explained the relationship between motivation, ability, and opportunity to consumer innovativeness and consumer attitude. This research was conducted on consumers of Skincare services in Indonesia. This research used structural equation model by using software WARP PLS 6.0 to prove the hypothesis. The result of this research showed that consumer innovativeness was a positive effect on consumer attitude. And supply chain had a role as moderator variable to the relationship between consumer innovativeness and consumer attitude. The implication of this research was expected to be useful for a service business that prioritizes in service innovation. By knowing the characteristics of its consumers through motivation, ability, and opportunity innovativeness.